2018
DOI: 10.1186/s13104-018-3290-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of infection by Chikungunya, Zika, and Dengue in an area of the Peruvian coast. Molecular diagnosis and clinical characteristics

Abstract: ObjectiveTo assess the presence of Dengue, Chikungunya, and Zika in serum samples of patients with acute febrile illness in Piura, Peru and describe the most common clinical features.ResultsDengue was the most common arbovirus detected in 170/496 (34.3%), followed by Zika in 39/496 (7.9%) and Chikungunya in 23/496 (4.6%). Among the 170 samples positive for Dengue, serotype 2 was the most predominant type present in 97/170 (57.1%) of samples, followed by the serotype 3 in 9/170 (5.3%). Headaches, muscle pain, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
(21 reference statements)
1
17
0
3
Order By: Relevance
“…In the case of LAMP assays for ZIKV detection, it is important that analytical specificity be assessed in the presence of other mosquito-borne arboviruses found in the region. In the case of the most recent ZIKV outbreak in Latin America, this would include the arboviruses DENV 1-4, CHIKV, and YFV [87][88][89][90][91].…”
Section: Lamp Specificitymentioning
confidence: 99%
“…In the case of LAMP assays for ZIKV detection, it is important that analytical specificity be assessed in the presence of other mosquito-borne arboviruses found in the region. In the case of the most recent ZIKV outbreak in Latin America, this would include the arboviruses DENV 1-4, CHIKV, and YFV [87][88][89][90][91].…”
Section: Lamp Specificitymentioning
confidence: 99%
“…Clinical diagnosis does not reliably differentiate CHIKV infections from other etiologies on the differential, such as other alphaviruses (MAYV, ONNV), flaviviruses (most commonly DENV and ZIKV), and nonviral pathogens, which include, but are not limited to, Plasmodium species, Leptospira, rickettsia, and Salmonella. In settings of CHIKV cotransmission with DENV and ZIKV, a presumptive diagnosis of chikungunya was correct in only 10 to 40% of cases (7,8,31). Clinical prediction algorithms have been evaluated to differentiate CHIKV infections from infections with other etiologies, but these have not been independently validated in separate cohorts (59,63,66,72,76).…”
Section: Acute Clinical Presentation and Differential Diagnosismentioning
confidence: 99%
“…Attack rates have been relatively low in temperate regions (24), but rates as high as 50 to 75% have been reported during outbreaks in the tropics (25)(26)(27). Such high attack rates help explain the occurrence of human coinfections with CHIKV, DENV, and/or ZIKV, which have been reported from the Americas and Asia (7,(28)(29)(30)(31)(32)(33), and individuals with these coinfections may present with more severe manifestations (7,30). A meta-analysis of available publications on CHIKV coinfections revealed that CHIKV-DENV coinfections were most common (44/109 studies), but CHIKV-malaria coinfections were reported in several studies (5/109) (28,29,34).…”
mentioning
confidence: 99%
“…In Peru situation is similar, studies have reported the presence of the four serotypes of DENV in the Peruvian coast, being the serotype DENV 2 the most frequent during the period from May to August (i.e., in 2016), as well as the Zika virus (ZIKV) and the Chikungunya virus (CHIKV) [7]. In the last 3 years, the presence of the Oropouche virus (OROV) has been reported, reemerging in some areas such as Madre de Dios or recently appearing in other areas such as Huánuco [8,9].…”
Section: Introductionmentioning
confidence: 87%
“…In the first study, 496 samples from patients with Acute Febrile DiseaseIllness (AFI) were analyzed and DENV, CHIKV, or ZIKV were identified in 46.8% (232/496) of the samples. The current study was performed including the total number (496 samples) of patients who met the criteria of AFI (axillary temperature ≥ 38 °C for less than 7 days together with one or more the signs and/or symptoms associated with arbovirus infections described in previous works and developed later in the text [7,13]. We excluded samples in inadequate state of conservation, samples without codification, improperly filled data sheets and those with incomplete demographic data such as age, gender, place of origin, etc.…”
Section: Patients and Samplingmentioning
confidence: 99%